SYRIAN REFUGEES IN TURKEY AS AN EXAMPLE OF MIGRANT PROBLEM - Zeki BOYRAZ (Zeitschrift für die Welt der Türken, 2015)
The on going conflicts and wars in different parts of the world on different dates forced millions of people to migrate. Over 5 million Palestinians still live in the refugee camps built in Lebanon, Syria, Jordan and Paletsine after the war in 1967. Many Albanian, Kosovan, Bosnian, Iraqi and Somalian migrated to various European countries and NortAmerica. Our kins took refuge in our country due to the political oppression they experienced in the balkan states likeGreece, Bulgaria, Romania and Jugoslavia. They still live in our country, particularly in the Marmara region. The main reason of Syrian migration was the armed struggle between the Syria Baas Party and the opponent party who wanted to come to power. The struggle started on March 15th, 2011 and spread all over the country in April, 2011. Consequently, 7.6 million Syrian had to migrate. 1.532 of these Syrian took refuge in Turkey. 235.000 of these migrants live in tent cities in different cities and 1.332 of these migrants dispersed all over the country. Our study takes the Syrian migration toTurkey as an example to draw attention on the migrants and refugees who are forced to migrate because of wars, civil wars and political oppression in their countries. In our study the dispersion of tent cities in Turkey will be examined taking the camps in Akçakale as an example. It’s clear that this Syrian refugee crisis will cause Syrian migrants to be settled in Turkey in the near future.